The Correlation between Students Self Efficacy in Writing Descriptive Text and Their Writing Performance (RETAIN, 2022)
Writing performance is an aspect correlated significantly to writing as one of the essential part in the school curriculum. While writing self-efficacy is what students believe in the way they engaged with writing activities which is a multi-dimensions of linguistic self-efficacy, self-regulatory self-efficacy, and performance self-efficacy. Previous studies indicate that there is a significant correlation between students’ writing performance and their writing self-efficacy, but there is no research discussing it at secondary level of students. Thus, the current study is aimed to find out the writing self-efficacy level of secondary students and analyze whether there is any correlation between students writing' self-efficacy and their writing performance at secondary level, especially in writing descriptive text. The data are collected through conducting L2WSS survey on 20-40 eleventh grade students from SMA Negeri 1 Sumenep, valuing their writing performance using a Level-Specific Checklist of Binary Choice Items, and finally examining the correlation between writing self-efficacy and writing performance using SPSS 2016 program. The result shows that mean value of students writing self-efficacy is 4.83 from the range of 1-2 as the low level, 3-5 as the moderate, and 6-7 as the high, so it is considered as a moderate level of writing self-efficacy. While the correlational analysis shows significance value is 0.602 which is more than 0.05 (p>0.05), so that means there is no significance correlation between students writing self-efficacy and their writing performance at secondary level especially in writing descriptive text. Keywords: Writing, Writing Performance, Writing Self-Efficacy.